Mathematical study of the mean communication distances at lognormal shadow fading and Nakagami fading - Souparnika Subhash Jadhav; Nagesh K. N; Ravi Chaurasia (Institute of Advanced Engineering and Science, 2020)
Over some few decades, the communication distance and connectivity at wireless sensor network (WSN) has got noticeable attention from the researchers. In general, the communication process in WSN ad-hoc occurs without some wired infrastructure and, the communication process done through a ‘single-hop’ transmission, where the intermediate nodes called as relay nodes are used in long distance communication and the nodes are capable to transmit and receive the data packets. In this paper, we presented a computational analysis of communication distance in WSN in the presence of fading effects such as nakagami-m fading and lognormal fading. An extensive investigation at both nakagami-m fading and lognormal fading is carried out to provide optimize communication in ad-hoc WSN. In addition, individual wireless nodes have the similar range of communication, is assumed to get the precise communication distance and coverage area in a WSN, where it is required to get mean communication distance. In result analysis section, several validation parameters such as transmitted power, attenuation constant and different number of fading factor is considered to provide proper analytical view.